Influence of Foliar Fungicide Treatment on Lipolytic Enzyme Activity of Whole Wheat. Issue 3 (7th February 2017) - Poudel, Rachana; Bhatta, Madhav; Regassa, Teshome; Rose, Devin J.
Abstract : Lipolytic enzymes play a key role in the deterioration of whole wheat flour upon storage but may also be involved in plant disease and stress tolerance while the crop is in the field. Therefore, the purpose of this study was to determine the effect of foliar fungicide treatment on lipolytic activity in wheat. A significant cultivar × fungicide × year interaction for esterase ( p ‐nitrophenyl butyrate as substrate [EA‐B]) and lipoxygenase (LOX) activities was observed; however, a large portion of the variability was owing to year (environment). Fungicide influenced lipase (olive oil as substrate [LA‐O]), EA‐B, and LOX activities. Lipase ( p ‐nitrophenyl palmitate as substrate [LA‐P]) showed variation in terms of cultivar and year rather than the application of fungicide. Partial correlation (year as a partial variable) between LA‐P and EA‐B activities was observed ( r = 0.78, P < 0.001), although neither was correlated with LA‐O. The influence of foliar fungicide on lipolytic enzyme activities depends mostly on growing conditions but is also affected by disease stress, disease resistance of the varieties tested, and the substrate being used in the assay.